O insumo linguístico oral em aulas de inglês como língua estrangeira para crianças: a fala do professor em foco - Colombo, Camila Sthéfanie [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
This research study investigates the oral linguistic input provided by Brazilian teachers in classes of English as foreign language (EFL) for children of an average age of eight years old, that is, children coursing the second year of primary school in three contexts: regular public school, regular private school and language school. The nature of this research is qualitative with an ethnographic approach, using the following instruments to gather data: notes and field diaries, interviews, audio recordings and transcriptions of classes taught in the three contexts mentioned above, and didactic materials analysis. The investigation is based on the input hypothesis suggested by Krashen (1987) and on the input-interaction-production (IIP) model elaborated by Gass (1997), Long (1996) and Skeham (1998). Studies concerning teacher education and the competences required to teach foreign language for children (SANTOS, 2009, 2010, 2013; CONSOLO, 1996, 2006, 2007, 2008, 2011; among others), teacher talk (MACHADO, 1992; CONSOLO, 1996; ARAÚJO, 2009; CUNHA; MANESCHY, 2011; among others); the role of vocabulary in classes of FL(C) (NATION, 1990; CAMERON, 2001.; ZILLES, 2001; among others); the importance of speaking in the teaching of FL(C) (CAMERON, 2001, 2003; CONSOLO, 1996); and teaching and learning approaches (HOLLIDAY, 1994; SANTOS, 2009, 2010; SILVESTRE, 2007; among others) also contribute to the research. The results obtained suggested that the construction of speaking in classes and, consequently, the offering of oral linguistic input happened via a mirroring of the language samples provided by the materials that oriented the traditionally structured classes. The referred offering was given by means of facilitating and facilitated talk and by the use of frequent repetitions. The samples were composed of vocabulary representative of low sophistication, low variety, low complexity and, consequently, high density, being offered in extreme ...

Neste trabalho, investiga-se o insumo linguístico oral oferecido por professores brasileiros em aulas de inglês como língua estrangeira (ILE) a crianças – com idade média de oito anos, ou seja, integrantes do segundo ano do ensino fundamental na escola de ensino básico – em três contextos: escola regular pública, escola regular privada e escola de idiomas. Trata-se de uma pesquisa de natureza qualitativa, de cunho etnográfico, em que são utilizados, para obtenção de dados, os seguintes instrumentos: anotações e diários de campo, entrevistas, gravações em áudio e transcrições de aulas ministradas nos três contextos, e análise de materiais didáticos. A pesquisa fundamenta-se na hipótese do insumo proposta por Krashen (1987) e no modelo insumo-interação-produção (IIP) elaborado por Gass (1997), Long (1996) e Skeham (1998). Contribuem para a investigação estudos referentes à formação docente e às competências linguísticas necessárias para atuação no ensino de LE(C) (SANTOS, 2009, 2010, 2013; CONSOLO, 1996, 2006, 2007, 2008, 2011; dentre outros), à fala docente (MACHADO, 1992; CONSOLO, 1996; ARAÚJO, 2009; CUNHA; MANESCHY, 2011; dentre outros); ao espaço destinado ao vocabulário nas aulas de LE(C) (NATION, 1990; CAMERON, 2001.; ZILLES, 2001; dentre outros); à importância da oralidade no trabalho com LE(C) (CAMERON, 2001, 2003; CONSOLO, 1996); e às abordagens de ensino-aprendizagem de línguas (HOLLIDAY, 1994; SANTOS, 2009, 2010; SILVESTRE, 2007; dentre outros). Os resultados obtidos mostram que a construção da oralidade nas aulas e, por extensão, o oferecimento de insumo linguístico oral ocorria por meio de um espelhamento das amostras de língua(gem) oferecidas pelos materiais didáticos que orientavam as aulas tradicionalmente estruturadas. Tal oferta se dava por meio de fala facilitada e facilitadora e de empregos frequentes de repetições, de modo que as amostras eram compostas por vocábulos ...
Keywords: Linguistica aplicada; Professores de ingles - Formação; Língua inglesa - Estudo e ensino; Ensino fundamental; Applied linguistics